LIVING CALCAREOUS ALGAE BY A PALEONTOLOGICAL APPROACH: THE GENUS LITHOTHAMNION HEYDRICH NOM. CONS. FROM THE SOFT BOTTOMS OF THE TYRRHENIAN SEA (MEDITERRANEAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Living non-geniculate corallinacean algae recovered in the Tyrrhenian Sea  (Tuscan Archipelago, Pontian Islands and Egads) have been collected at 53 stations ranging in depth from 27 down to 137 m and in the maërl of Marettimo (Egads) at 30-35 m depth. L. corallioides has been collected at Marettimo and in 10 stations ranging from 44 to 93 m depth. Z. fruticulosum auctorum has been redescribed and identified as L. minervae sp. nov., collected at Marettimo and in 23 stations ranging from 27 to 98 m depth. L. philippii Foslie has been identified in 5 stations ranging from 45 and 79 m depth.  L. valens Foslie has been recognized at Marettimo and in 9 stations from 51 to 79 m depth, with maximum abundance and best developed specimens collected in the channel between the islands of Ponza and Palmarola. The diagnostic elements of the thallus of the four species are described by SEM and OM images and biometric  data. The zonation of the thallus, due to alternating bands of thick-walled and thin-walled cells, is described in details for L. corallioides,  L. minervae and  L. valens.
Keywords: Taxonomy; Calcareous algae; Corallinaceae; Recent; Tyrrhenian Sea.